Using Group Communication to Support Inter-Vehicle Co-ordination - O'Gorman, Eoin (Trinity College Dublin. Department of Computer Science, 2002)
Recent advancements in wireless communication technology and portable computing are opening up exciting possibilities for the future of mobile network applications. One obvious domain for such mobile network applications is in vehicle traffic scenarios, where vehicle-mounted mobile hosts, with wireless communication ability, form an ad hoc network. With the aim of improving transportation systems, through the reduction of road accidents, inter-vehicle coordination applications are being built upon these vehicle-based ad hoc networks. This dissertation is concerned with investigating the use of group communication to support inter-vehicle coordination applications in ad hoc networks. Specifically, one particular case study of inter-vehicle coordination is examined: the 4 Way Stop. A 4 Way Stop is a common road junction, with four approaching roads, of equal importance, meeting at a single point. The problem of a 4 Way Stop is in determining which vehicle should be allowed to cross the junction at any one time. This dissertation identifies the requirements on group communication to successfully support a 4 Way Stop application. Requirements for optional group communication application implementations: primary component implementation and partitionable membership implementation are both listed. Moving from the specific to the general, the examination of a 4 Way Stop application provides valuable insights into the general domain of inter-vehicle coordination.
Keywords: Computer Science